21-gene recurrence score and adjuvant chemotherapy decisions in patients with invasive lobular breast cancer. (19th December 2018) - Chen, Xiang-Hong; Zhang, Wen-Wen; Wang, Jun; Sun, Jia-Yuan; Li, Feng-Yan; He, Zhen-Yu; Wu, San-Gang
Aim: To determine the effect of the 21-gene recurrence score (RS) on outcome and chemotherapy decision in breast invasive lobular carcinoma (ILC).Materials & methods: We included 6467 patients with early stage and estrogen receptor–positive ILC from the Surveillance, epidemiology, and end results database.Results: A total of 9.1, 31.4, and 70.1% of patients with low-, intermediate-, and high-risk RS groups received chemotherapy, respectively. A higher RS was independently associated with poor breast cancer-specific survival, and receipt of chemotherapy was not related to better breast cancer-specific survival in low-, intermediate-, or high-risk RS groups.Conclusion: The 21-gene RS could impact chemotherapy decision making in early-stage ILC. However, adjuvant chemotherapy does not appear to improve outcome in high-risk RS cohort.